2015
DOI: 10.5937/leksir1535163d
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal potential of Bacillus spp.: Isolates as biocontrol agents

Abstract: IZVODBolesti biljaka izazvane infekcijama patogenim gljivama mogu dovesti do smanjenja kapaciteta biljnog rasta ili naneti mnogo ozbiljniju štetu dovodeći do smrti biljaka i značajnih gubitaka u proizvodnji hrane. Veliki broj istraživanja je u poslednje vreme posvećen proučavanju sekundarnih metabolita koje proizvode vrste roda Bacillusa koji se mogu koristiti za kontrolu različitih biljnih patogena. U ovoj studiji prikazan je jak antifungalni efekat lipopeptidnih ekstrakata iz izolata roda Bacillus prema 11 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…One of the most commonly reported PGPR is Bacillus species. It has range of reported properties, including nitrogen fixation, P solubilisation, antibiotic and cytokinin production (Hu et al, 2019;Singh et al, 2015;Fira et al, 2018;Dimkic et al, 2015). It is also reported that Bacillus isolates can increase root and shoot growth of wheat (Knezevic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly reported PGPR is Bacillus species. It has range of reported properties, including nitrogen fixation, P solubilisation, antibiotic and cytokinin production (Hu et al, 2019;Singh et al, 2015;Fira et al, 2018;Dimkic et al, 2015). It is also reported that Bacillus isolates can increase root and shoot growth of wheat (Knezevic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%